1992
DOI: 10.1287/mnsc.38.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Locally Rational Decision Making: The Distracting Effect of Information on Managerial Performance

Abstract: This paper describes a phenomenon called "locally rational" decision-making, in which the mere presence of information may have dysfunctional consequences even if decision makers do not process the information incorrectly. Using the results from an experiment conducted with a strategic market simulation game, we find that the accessibility of information results in a disposition to focus on those components of decision-making most clearly addressed by the information. If these are not the components most close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 15 publications
3
80
1
3
Order By: Relevance
“…These findings support the view that the competitive advantage associated with information depends less on whether a firm has information and increasingly on whether a firm is able to make the best use of that information (Glazer 1991;Porter and Millar 1985). However, further research should formally investigate whether the utilization processes are mediating the impact of information acquisition and transmission processes.…”
Section: Cultural Antecedents Of Organizational Market Information Prsupporting
confidence: 70%
See 1 more Smart Citation
“…These findings support the view that the competitive advantage associated with information depends less on whether a firm has information and increasingly on whether a firm is able to make the best use of that information (Glazer 1991;Porter and Millar 1985). However, further research should formally investigate whether the utilization processes are mediating the impact of information acquisition and transmission processes.…”
Section: Cultural Antecedents Of Organizational Market Information Prsupporting
confidence: 70%
“…Furthermore, it was suggested that how culture influences organizational information processes may be note that many researchers consider culture and climate to be synonymous. The finding that new product performance is promoted by instrumental utilization processes supports the linkages that previous research has made between firms' intensifying their adoption of information processes and the effectiveness of firm outputs (Glazer 1991). Moreover, the fact that conceptual utilization processes are also predictive of new product performance contributes to the extant research that rarely measures these processes and has had limited success in detecting their effects (Rich 1981;Weiss and Bucuvalus 1980).…”
Section: Cultural Antecedents Of Organizational Market Information Prsupporting
confidence: 59%
“…Moreover, when overloaded with information and faced with ever increasing quantities of intelligence, the decision-maker cannot direct sufficient attention to interpret and sift the information to identify priorities and best responses. The effect is compromise in the design and execution of responses to market change (Glazer et al, 1992;Souchon et al, 2004). …”
Section: Hypothesesmentioning
confidence: 99%
“…In essence, the responses of decision-makers are unlikely to be optimal because these decision-makers are forced to filter the abundance of information that confronts them (Ocasio, 1997). It is this filtration process that can distort responsiveness in the manner put forward by Glazer, Steckel, and Winer (1992), Souchon et al (2004), and Vyas and Souchon (2003) among others.…”
Section: Hypothesesmentioning
confidence: 99%
“…Past research has demonstrated that experienced decision makers exhibit better judgments than novices, but they do so without using more information (see, e.g., Connolly and Gilani, 1982;Shanteau, 1992). Some research has shown that experienced decision makers are in fact distracted by too much information, and that too much information can interfere with decision making (Gaeth and Shanteau, 1984;Glazer et al, 1992). In information systems development in particular, some studies focusing on differences between experienced and novice analysts have shown that experience is an indicator of improved performance (Davis, 1982;Schenk et al, 1998;Walz et al, 1993).…”
Section: The Impact Of Analyst Experience On Information Gatheredmentioning
confidence: 99%